Further explorations of illness uncertainty: carers' experiences of Parkinson's disease. Issue 5 (4th May 2017) - Hurt, Catherine S.; Cleanthous, Sophie; Newman, Stanton P.
Abstract : Objective : Dominant models of illness uncertainty define uncertainty as 'an inability to determine the meaning of illness-related events'. Recent research has shown patient uncertainty to be multidimensional encompassing personal issues indirectly affected by illness. The nature of carer uncertainty has yet to be fully explored. The present study aimed to investigate the nature of illness uncertainty in the carers of patients with Parkinson's disease (PD). Design : Eighteen carers of a spouse with PD participated in semistructured interviews. Transcripts were thematically analysed, statements were coded as uncertain if they reflected 'a lack of certainty, or a state of limited knowledge, understanding or worry regarding an existing or future outcome'. Results : The domains of uncertainty expressed by carers closely fitted the five domain framework of patient uncertainty: symptoms and prognosis, medical management, self-management, social functioning and impact. An additional 'carer-role' domain was identified. Conclusions : Carer uncertainty about PD went beyond issues directly related to the illness. The findings have implications for research into uncertainty suggesting that widely used measures may not be accurately capturing the nature of carer uncertainty about chronic illness. The breadth of uncertainty reported has implications for the provision of appropriate support to improve caregiver well-being.